2017
DOI: 10.1183/13993003.01044-2017
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosistransmission from patients with drug-resistant compared to drug-susceptible TB: a systematic review and meta-analysis

Abstract: The extent to which drug-resistant (DR) Mycobacterium tuberculosis strains cause infection and progression to tuberculosis (TB) disease in comparison to drug-susceptible (DS) strains is unknown. Studies in guinea pigs and in vitro experiments have suggested a reduced fitness of organisms that harbour mutations that confer drug resistance [1,2]; it was therefore believed that transmitted drug resistance was a rare event. However, more recent work using molecular typing has shown transmission events occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, in-vitro competition assays have shown fitness differences between strains with and without resistance, albeit in highly artificial in-vitro experiments. 75 Studies into rates of infection or progression to disease in contacts of multidrug-resistant tuberculosis relative to drug-susceptible tuberculosis have yielded variable results, as described previously, 25 and molecular epidemiology studies defining transmission in terms of clustering of strains suggest lower fitness for resistant strains. 76…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in-vitro competition assays have shown fitness differences between strains with and without resistance, albeit in highly artificial in-vitro experiments. 75 Studies into rates of infection or progression to disease in contacts of multidrug-resistant tuberculosis relative to drug-susceptible tuberculosis have yielded variable results, as described previously, 25 and molecular epidemiology studies defining transmission in terms of clustering of strains suggest lower fitness for resistant strains. 76…”
Section: Introductionmentioning
confidence: 95%
“…Contact investigation studies are another approach to measuring the relative infectiousness of drug-resistant tuberculosis cases. A recent meta-analysis, 25 assessing whether M tuberculosis transmission and progression to tuberculosis disease differ between drug-resistant and drug-susceptible tuberculosis, found a greater likelihood of M tuberculosis infection in contacts of drug-resistant tuberculosis index patients compared with drug- susceptible tuberculosis index cases, but no difference in risk of tuberculosis disease. This increase in the number of infected contacts of drug-resistant index cases could be due to prolonged duration of infectiousness in drug-resistant tuberculosis as a result of diagnostic delays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current analysis does not explore the economic impact of TB transmission dynamics. Each untreated or failing patient continues to transmit the disease and expands the reservoir of potential future XDR-TB cases [59,60]. An assessment of the economic impact of stemming transmission of DR-TB should be undertaken to provide a broader understanding of the cost-effectiveness discussion in the public health context.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Meta analyses of MDRTB contact tracing studies have shown that 41.3–61.3% of household contacts have latent TB infection, and that 3.4–6.5% develop active disease [ 13 15 ]. Despite significant heterogeneity in the studies included in these systematic reviews they have consistently identified a substantial yield of secondary tuberculosis cases among household and close contacts.…”
Section: Introductionmentioning
confidence: 99%